Diagnosis of cancer as an emergency: a critical review of current evidence - Zhou, Yin; Abel, Gary A.; Hamilton, Willie; Pritchard-Jones, Kathy; Gross, Cary P.; Walter, Fiona M.; Renzi, Cristina; Johnson, Sam; McPhail, Sean; Elliss-Brookes, Lucy; Lyratzopoulos, Georgios (Nature reviews. Clinical oncology, 2017)
Key Points The diagnosis of cancer as an emergency is associated with a substantially worse prognosis; however, this represents an understudied problem, with evidence examining its frequency and aetiology limited to a few developed countries Most available evidence defines diagnosis of cancer as an emergency contextually instead of employing clinical criteria regarding presentation severity, and uses administrative data as opposed to reviews of medical records An emergency diagnosis of cancer often has a complex aetiology, involving tumour, patient and health-care related factors; evidence on the role of tumour and health-care related factors is particularly sparse Studying variations in the risk of emergency presentations by prior health-care use and related symptoms can elucidate how some emergency presentations could potentially be prevented Sociodemographic inequalities in the risks of emergency presentation underline the contribution of psychosocial factors and the potential for targeting of public health campaigns regarding cancer symptoms Optimising screening can help to reduce emergency presentations of patients with colorectal cancer Patients diagnosed with cancer through an emergency presentation have worse outcomes compared with those in whom cancer is diagnosed through other routes; therefore, reducing the number of patients presenting as an emergency with cancer will improve patients' outcomes. In this Review, the authors describe the available evidence in this area, and provide recommendations for future research, clinical practice and public health policy. Many patients with cancer are diagnosed through an emergency presentation, which is associated with inferior clinical and patient-reported outcomes compared with those of patients who are diagnosed electively or through screening. Reducing the proportion of patients with cancer who are diagnosed as emergencies is, therefore, desirable; however, the optimal means of achieving this aim are uncertain owing to the involvement of different tumour, patient and health-care factors, often in combination. Most relevant evidence relates to patients with colorectal or lung cancer in a few economically developed countries, and defines emergency presentations contextually (that is, whether patients presented to emergency health-care services and/or received emergency treatment shortly before their diagnosis) as opposed to clinically (whether patients presented with life-threatening manifestations of their cancer). Consistent inequalities in the risk of emergency presentations by patient characteristics and cancer type have been described, but limited evidence is available on whether, and how, such presentations can be prevented. Evidence on patients' symptoms and health-care use before presentation as an emergency is sparse. In this Review, we describe the extent, causes and implications of a diagnosis of cancer following an emergency presentation, and provide recommendations for public health and health-care interventions, and research efforts aimed at addressing this under-researched aspect of cancer diagnosis.